Competition-induced visual field differences in search. - Fecteau, Jillian H.; Enns, James T.; Kingstone, Alan (Psychological Science., 2000)
A study was conducted to examine competition-induced visual field differences in search. Data were drawn from assessment of three attributes of visual search—competition, task specialization, and anatomical alignment. Findings reveal that in terms of competition, the visual field differences in search efficiency are larger in whole- than in half-field displays; in terms of task specialization, that some tasks favor one hemisphere, but other tasks favor the other hemisphere; and in terms of anatomical alignment, that that competition effects change if the quadrants of the visual display are not aligned with the cortical quadrants of the observer.